The inevitable perversion of technological advances under capitalism: higher productivity and greater labour exploitation (Sociología y tecnociencia, 2022)
One need only think of areas such as information technology, telecommunications, nanotechnology, biotechnology, robotics or so‐called artificial intelligence, among others, to identify the indisputable fact that in recent decades there have been enormous scientific and  technical  advances,  linked  to  increased labour productivity. Without looking at the social reality, it  might  be  thought  that,  "as  a consequence",  the  living  conditions  of  the world's population as a whole have improved considerably.
Keywords: technology; artificial intelligence; capitalism; labor market; productivity